Delta- and gamma-tocotrienol isomers are potent in inhibiting inflammation and endothelial activation in stimulated human endothelial cells - Abd Manaf, Ali; Suhaila, Muid; Hapizah, Mohd Nawawi (2016)
Background: Tocotrienols (TCTs) are more potent antioxidants than a-tocopherol (TOC). However, the effectiveness and mechanism of the action of TCT isomers as anti-atherosclerotic agents in stimulated human endothelial cells under inflammatory conditions are not well established.